Overexpression of CTLA-4 and fibronectin, and lower expression of CD137 (4-1BB) is associated with brain metastasis of primary skin melanomas. An analysis of local immune response by digital spatial profiling - Najjary, Shiva; Amery, Nur al; Huang, Mengqi; Vadgama, Disha; van Akkooi, Alexander C. J.; Gilhuis, H. Jacobus; Belcaid, Zineb; Mustafa, Dana; Kros, Johan M. (Frontiers in Immunology, 2025)
BackgroundTo discover immune response-associated gene expressions related to brain metastases of skin melanomas, we analyzed a group of fifteen primary skin melanomas consisting of five tumors from patients who did not develop systemic metastases (NM); ten from patients with systemic metastasis of which five with (BM), and five without brain involvement (OOM). Regions of interest (ROIs) harboring tumor cells only; immune cells only; or immune cell infiltration in tumor cell regions, were separately analyzed.Methodswe profiled the tumor immune microenvironment (TIME) of primary skin melanomas by using a panel of 77 immune response-related oligo-nucleotide targets in the GeoMx Digital Spatial profiler (Nanostring Technologies).ResultsMelanomas from patients who developed brain metastases contained significantly higher levels of (CD45+) immune cells and overexpressed fibronectin and CTLA-4 in all ROIs compared to the melanomas that had metastasized to other sites than the brain (p<0.05). Distant metastases were accompanied by lower expression of CD137 (4-1BB). Downregulation of VISTA, IDO1 and ICOS was associated with melanomas that gave rise to distant metastases including brain.ConclusionLower expression of CD137 (4-1BB) is linked with the formation of distant metastases and the expressions of fibronectin and CTLA-4 herald the formation of brain metastasis in particular.